Increased Coronary Artery Disease Severity in Black Women Undergoing Coronary Bypass Surgery. Issue 7 (February 2015) - Efird, Jimmy T.; O'Neal, Wesley T.; Griffin, William F.; Anderson, Ethan J.; Davies, Stephen W.; Landrine, Hope; O'Neal, Jason B.; Shiue, Kristin Y.; Kindell, Linda C.; Bruce Ferguson, T.; Randolph Chitwood, W.; Kypson, Alan P.
Abstract : Abstract: Race and sex disparities are believed to play an important role in heart disease. The purpose of this study was to examine the association between race, sex, and number of diseased vessels at the time of coronary artery bypass grafting (CABG), and subsequent postoperative outcomes. The 13, 774 patients undergoing first-time, isolated CABG between 1992 and 2011 were included. Trend in the number of diseased vessels between black and white patients, stratified by sex, were analyzed using a Cochran–Armitage trend test. Models were adjusted for age, procedural status (elective vs. nonelective), and payor type (private vs. nonprivate insurance). Black female CABG patients presented with an increasingly greater number of diseased vessels than white female CABG patients (adjusted P trend  = 0.0021). A similar trend was not observed between black and white male CABG patients (adjusted P trend  = 0.18). Black female CABG patients were also more likely to have longer intensive care unit and hospital lengths of stay than other race–sex groups. Our findings suggest that black female CABG patients have more advanced coronary artery disease than white female CABG patients. Further research is needed to determine the benefit of targeted preventive care and preoperative workup for this high-risk group.